Effects of symptom versus recovery video, similarity, and uncertainty orientation on the stigmatization of schizophrenia. (1st February 2017) - Li, Yixian; Sorrentino, Richard M.; Norman, Ross M.G.; Hampson, Elizabeth; Ye, Yang
Abstract: 191 participants either watched a video of a person with schizophrenia who discussed his recovery or the symptoms he experienced when acutely ill. Participants were asked to focus either on similarities or differences between themselves and the person depicted. Uncertainty orientation, the extent to which people prefer to resolve uncertainty (uncertainty-orientated) or avoid it in order to main certainty (certainty-orientated) was assessed for each participant. Results showed that for explicit attitudes, the recovery video and uncertainty orientation were significantly associated with more positive responses. The similarity manipulation interacted with video content and uncertainty orientation in influencing implicit attitudes. As expected, compared to those who are uncertainty-oriented, participants who are certainty-oriented were more likely to hold positive implicit attitudes after watching the recovery than symptoms video, particularly when attending to similarities. Highlights: Different videos led to varied explicit responses to people with schizophrenia. Differences in people's uncertainty orientation led to varied explicit responses. The former two interacted with a similarity focus to influence implicit attitude. Perceived similarity may have mediated the effects on explicit responses.